2022
DOI: 10.3390/cells11182873
|View full text |Cite
|
Sign up to set email alerts
|

Hashimoto Encephalopathy—Still More Questions than Answers

Abstract: The normal function of the nervous system is conditioned by the undisturbed function of the thyroid gland and its hormones. Comprehensive clinical manifestations, including neurological disorders in Hashimoto’s thyroiditis, have long been understood and, in recent years, attention has been paid to neurological symptoms in euthyroid patients. Hashimoto encephalopathy is a controversial and poorly understood disease entity and the pathogenesis of the condition remains unclear. We still derive our understanding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 120 publications
0
21
0
Order By: Relevance
“…Using a specific marker for Hashimoto’s thyroiditis is essential in terms of making early and accurate diagnosis and preventing possible complications of Hashimoto’s thyroiditis as a result of hypothyroidism. These complications can be listed, such as heart diseases [ 51 ], depression [ 52 ], birth defects [ 53 ], dyslipidemia [ 54 ], and Hashimoto encephalopathy [ 55 ]. The PLR could provide useful diagnostic value as an additional diagnostic tool in the establishment of HT diagnosis at the earliest time, which can decrease the rate of HT complications.…”
Section: Discussionmentioning
confidence: 99%
“…Using a specific marker for Hashimoto’s thyroiditis is essential in terms of making early and accurate diagnosis and preventing possible complications of Hashimoto’s thyroiditis as a result of hypothyroidism. These complications can be listed, such as heart diseases [ 51 ], depression [ 52 ], birth defects [ 53 ], dyslipidemia [ 54 ], and Hashimoto encephalopathy [ 55 ]. The PLR could provide useful diagnostic value as an additional diagnostic tool in the establishment of HT diagnosis at the earliest time, which can decrease the rate of HT complications.…”
Section: Discussionmentioning
confidence: 99%
“…Also, researchers are becoming more interested in Alzheimer's disease and Hashimoto's encephalopathy as they relate to cognitive impairment. However, the current research on these two diseases does not give a clear picture of how adult hypothyroidism is linked to cognitive impairment (22).…”
Section: Hypothyroidism and Cognitive Impairment In Adultsmentioning
confidence: 98%
“…A large-scale study showed that individuals with hypothyroidism faced a higher risk of memory impairment (up to 81%), higher perceived stress, more than a 3-fold increase in dementia risk, higher rates of depression and anxiety, greater fatigue, poorer concentration, and less motivation [ 8 ]. Some rare cases of autoimmune thyroiditis could lead to Hashimoto’s encephalopathy, presented by nonspecific clinical manifestations rapidly leading to progressive dementia, reversed by corticosteroid therapy [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%